Electrical resistivity, thermal stability and tensile strength of rice husk flour-plastic waste composites / Shahril Anuar Bahari, Kamrie Kamlon and Masitah Abu Kassim - Bahari, Shahril Anuar; Kamlon, Kamrie; Abu Kassim, Masitah (Research Management Institute, 2012)
In this study, the rice husk flour-plastic waste composites (RPC) was produced from polypropylene (PP) and high density polyethylene (HDPE) wastes with 30 and 50% rice husk flour (RHF) contents. RPC was made by melt compounding and compression moulding processes. The electrical resistivity, thermal stability and tensile strength of RPC were determined. The RPC was tested in electrical resistivity and tensile strength according to the ASTM D-257 and ASTM D-638 respectively, while thermal stability was tested using thermogravimetric analysis (TGA) method. From the results, high content of RHF reduces all properties, except for tensile modulus of elasticity (TMOE) in tensile strength test. The ability of moisture absorption and the presence of hemicelluloses, cellulose and silica in RHF reduce the electrical resistivity and thermal stability behaviour of RPC from 50% RHF. The good binding elements and filler agglomeration in RPC from 50% RHF improve only TMOE. Insufficient stress transfer and rigid interphase occurred between RHF and plastics during tensile maximum load and elongation at break (Eb) in tensile strength test. In general, RPC from HDPE indicates better thermal stability, tensile modulus of rupture and Eb (in tensile strength test) compared to PP, based on the good behaviour of thermal conductivity, low water absorption, high molecular weight and good elongation properties of HDPE. However, RPC from PP shows good electrical resistance due to the low thermal expansion coefficient of PP.